Global burden of hand osteoarthritis in adults aged ≥55 years - Xiaozong Lin; Wenyan Zhang; Bowen Wu; Mengyao Zhao; Duancen Liu; Maoqing Wang; Dongyu Hou; Jinpeng Zhuang (Medicine, 2026)
Among osteoarthritis (OA) subtypes, hand osteoarthritis (HOA) is the fastest-growing by estimated annual percentage change in age-standardized rates and percentage change in case numbers. Yet its burden in adults aged ≥55 years, who are disproportionately affected, has not been systematically quantified. Using Global Burden of Disease 2021 data, we assessed the global burden of HOA in this age group. Trends were analyzed using estimated annual percentage change and percentage change, and future projections were made using an autoregressive integrated moving average model. From 1990 to 2021, incident cases, prevalent cases, and years lived with disability (YLDs) in this age group increased by 3.13 million, 95.32 million, and 2.99 million, accounting for 51.40%, 80.80%, and 79.95% of total increases in the general population, respectively. In 2021, there were 5.13 million incident cases, 154.68 million prevalent cases, and 4.86 million YLDs, representing 49.52%, 79.61%, and 78.77% of the global burden, respectively, with corresponding age-standardized rates of 2.89, 4.71, and 4.66 times those in the general population. China, India, the United States, Japan, Russia, and Brazil together accounted for over 54% of incident cases, prevalent cases, and YLDs. By 2050, incident cases, prevalent cases, and YLDs are projected to reach 8.99 million, 292 million, and 8.96 million, respectively, with corresponding age-standardized rates of 2.57, 5.13, and 5.01 times those in the general population. The growth in HOA burden in this age group over the past 3 decades and through 2050 exceeds that of other osteoarthritis subtypes. The burden of HOA in adults aged ≥55 years is disproportionately high and is increasing faster than any other osteoarthritis subtype, with 6 countries (China, India, the United States, Japan, Russia, and Brazil) bearing the heaviest absolute burden. Thus, HOA in this age group has emerged as a global challenge demanding sufficient attention.